2000
DOI: 10.1111/j.1478-4408.2000.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

The application of chitosan in pigment printing

Abstract: The use of chitosan as a combined thickener and binder in pigment printing has been examined in comparison with a commercial printing system (Alcoprint). Printing pastes made up from mixtures of chitosan, pigment and acetic acid at the appropriate viscosity gave satisfactory prints on polyester and 67:33 polyester/cotton woven fabrics. Rheological data showed the chitosan pigment paste had a much lower yield point than commercial printing paste though no difficulties were found in its use. Curing of the chitos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 5 publications
1
32
0
Order By: Relevance
“…Apart from increasing the colour strength of fabrics with synthetic dyes (Julia, Pascual, & Erra, 2000;Sang-Hoon & Samuel, 2004), they also established the application as an auxiliary in printing of textiles. It has been reported that the printed samples have comparable colour fastness to that of commercial printed samples but for its stiffness of the fabrics (Bahmani, East, & Holme, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from increasing the colour strength of fabrics with synthetic dyes (Julia, Pascual, & Erra, 2000;Sang-Hoon & Samuel, 2004), they also established the application as an auxiliary in printing of textiles. It has been reported that the printed samples have comparable colour fastness to that of commercial printed samples but for its stiffness of the fabrics (Bahmani, East, & Holme, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Also application of natural dye prints as antibacterial finish has also remained unexplored. The applications of chitosan for different applications in textiles are reported [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], but the application of such functional biopolymer as a mordant in natural dyeing has been quite rare in the literature. In the current work, chitosan extracted from waste shrimp shells [24] was utilized as a mordant for simultaneous natural dye printing and antibacterial finishing of cotton in comparison with commonly used metal mordants.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin and its derivative chitosan are thought to have more than two hundred uses in areas as diverse as agriculture, biomedicine, cosmetics, food, textiles, as well as the potential for use as chelating agent and in refining industrial effluents (Bahmani et al 2000;Ravi Kumar 2000;Rinaudo 2006;Aranaz et al 2009). Currently, the most available source of chitin is the exoskeletons of crustaceans, particularly shrimps and crabs (Minke & Blackwell 1978;Acosta et al 1993).…”
mentioning
confidence: 99%